The study of knowledge, attitude and practice about abortion and technology at the tertiary centre in the region of Mewar, Rajasthan, India - Bamniya, Archana; Verma, Savitri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Availability of safe, effective and acceptable abortion-care services is one of the most important aspects of women’s reproductive health. Unsafe abortion is one of the four main causes of maternal mortality and morbidity. To study knowledge, attitude, and practice (KAP) regarding abortion and methods used among/for women of child bearing age to formulate recommendation for improving the safe abortion services Methods: This prospective study was done among 100 cases who came for MTP at department of Obstetrics and Gynaecology, RNT medical college, Udaipur during November and December 2017. Data was collected using a self-semi structured questionnaire related to abortion technology. Results: 58% of women knew that there were provisions for abortion in public hospitals but only 38% of them knew that abortion should be performed/carried out by a trained doctor only. 70% of the women knew that there were medicines available for abortion (MMA) but only 20% of them knew how and from where to avail them. 69% knew about other methods and that D and E can be done in hospitals both at private and public sector, 25% knew the complications related to unsafe abortion. About the attitude almost all women wanted abortion should be done if needed only 10% knew that abortion is legal. 66% of women consider MMA to be safe and 27% of women consider contraception is necessary. Conclusions: Majority of women have positive attitude towards the abortion. The most prefer method chosen for abortion was medical method of abortion (MMA).